Association among inflammaging, body composition, physical activity, and physical function tests in physically active women - Santos, Carlos Andre Freitas; Amirato, Gislene Rocha; Paixão, Vitoria; Almeida, Ewin Barbosa; Do Amaral, Jônatas Bussador; Monteiro, Fernanda Rodrigues; Roseira, Tamaris; Juliano, Yara; Novo, Neil Ferreira; Rossi, Marcelo; Alvares-Saraiva, Anuska Marcelino; Vieira, Rodolfo de Paula; et al. (Frontiers in Medicine, 2023)
Background: Inflammaging is a phenomenon that has been associated with development and progression of sarcopenia and frailty syndrome. According to the literature, whether on side, the increase in body fat is associated with a systemic pro-inflammatory status, which consequently favors inflammaging, on the other side, the regular practice of physical exercise can mitigate the development of this scenario. Therefore, here, we aimed to evaluate the association between inflammaging and physical factors, both body and functional, in a group of physically active older women. Methods: Seventy older women (mean age 72.66±6.17 years) participated in this observational cross-sectional and were separated into the eutrophic, overweight, and obese groups. It was assessed: by bioimpedance - body fat percentage (Fat%) and total (Fat kg), skeletal muscle mass (muscle), and free fat mass both in percentage (FFM%) and total (FFMkg); by the International Physical Activity Questionnaire (IPAQ) - the time of moderate-intensity physical activity per week; by physical tests - handgrip (HG), sit-up-stand-on-the-chair in 5 repetitions (Sit-up) and vertical squat jump test (SJ); besides the determination of serum cytokines concentration (IL-6, TNF-α, IL-10, and IL-8), and also Body Mass Index (BMI) and calf circumference (Calf). Results: Higher FFM% and lower body fat (both kg and %) were found in the eutrophic group than in the other groups. The eutrophic group also performed more weekly physical activity, jumped higher, and presented not only higher serum IL-6 concentration but also an increased ratio of IL-10/IL-6, IL-10/ TNF-α, IL10/IL-8 as compared to the values found in the overweight group. The obese group presented higher body fat (kg and %) and lower FFM% than the other groups and also higher serum IL-6 concentration than the overweight group. Interestingly, several significant negative and positive correlations between body composition, physical tests, and serum cytokine concentrations were found in the eutrophic and obese groups. Conclusions: Whilst the eutrophic older women group showed a remarkable regulation of the systemic inflammatory status with positive associations in the physical parameters assessed, the overweight and obese groups presented impairment regulations of the inflammaging, which could be related the less weekly physical activity and higher body fat.